RELATIONSHIP BETWEEN BLOOD PRESSURE AND URINE PROTEINS IN TYPE 2 DIABETES MELITUS PATIENTS IN KEDUNGMUNDU HEALTH CENTER - Devi Etivia Purlinda; Widodo Widodo (Jurnal Riset Kesehatan, 2020)
Hyperglycemia trigger complication in type 2 Diabetes Mellitus patients such as diabetic nephropathy which cause of end-stage kidney failure. Monitoring of blood glucose and blood pressure are part of self-management to prevent complications of diabetes. This study aim to determine the characteristics of type 2 DM prolanis patients at the Kedungmundu Health Center based on age, sex, duration of suffering, blood pressure, and blood glucose. In addition, the relationship of blood pressure and urine protein is also analysed in this study. This research use observational analytic design with cross-sectional approaching. The dependent and independent variables of this study are protein urine and blood pressure. Forty-six of DM patients are choosen as research’s object using purposive sampling technique. The data was analysed using chi-square. The results show that ratio between female and male type 2 diabetes patients are 71.7% to 28.3%. In addition, about 63% of the patients are suffering type 2 diabetes less than 5 years. The results inform us that 50% of type 2 diabetes patients are 56-65 years old, about 52.2% of them have hypertension, and 84.8% hyperglycemia. There is a significant relationship between blood pressure and urine protein with a p-value of 0.038 (p-value ≤ 0.05).